AB0372 Associated factors of cervical and lumbar spinal instability in patients with rheumatoid arthritis. (15th June 2017) - Sugimura, Y; Miyakoshi, N; Kashiwagura, T; Kobayashi, M; Aizawa, T; Aonuma, H; Shimada, Y
Abstract : Background: Few studies have compared rheumatoid arthritis (RA)-related disorders of the cervical and lumbar spine. Objectives: The objectives of this study were to examine the prevalence of and risk factors for cervical and lumbar spinal instability in patients with RA. Methods: From a total of 1, 843 patients registered in the Akita Orthopedic Group on Rheumatoid Arthritis (AORA), 135 patients [118 women, 17 men; mean age, 66 (41–84) years; mean disease duration, 14 (1–63) years] who underwent a radiographic examination were enrolled in this study. In the cervical spine, we defined instability as one of the following characteristics: (1) atlantodental interval (ADI) >3 mm, (2) Ranawat value <13 mm on a neutral plain radiograph, or (3) anteroposterior translation >3 mm at the subaxial cervical spine on an anteroposterior bending plain radiograph. In the lumbar spine, instability was defined as anteroposterior translation >3 mm on a neutral plain radiograph. At the time of radiographs evaluation, demographic characteristics, clinical variables, medical history and current medications were investigated. The patients were classified into two groups: with both cervical and lumbar spinal instabilities and without. The independent risk factors for both cervical and lumbar spinal instabilities were then determined using multivariate logistic regression analysis. Results: Forty-six (34.1%) patients exhibited cervical spinal instability, and 50 (37.0%) patients exhibited lumbar spinal instability. Twenty-four patients (17.8%) exhibited both cervical and lumbar spinal instability. The presence of both cervical and lumbar spinal instability was significantly and independently associated with disease duration (OR: 1.06; 95% CI: 1.01–1.12). Conclusions: The prevalence of both cervical and lumbar spinal instability in patients with RA was 17.8%. Disease duration was independent risk factor for presence of both cervical and lumbar spinal instability in this study. Disclosure of Interest: None declared